Types of damages on buffalo oocytes after vitrification with different concentration of ethylene glycol and dimethyl sulphoxide - DESHMUKH, S P; PAWSHE, C H; INGAWALE, M V; DESHMUKH, S G; KALE, S R (The Indian Journal of Animal Sciences, 2013)
The objective of the study is to observe the oocytes damage after vitrification in combination of ethylene glycol (EG) and dimethyl sulphoxide (DMSO) at different concentration with 1 and 3 min equilibration time (ET). A total 826 cumulus oocytes complexes were obtained by follicular aspiration from 278 ovaries of buffaloes, slaughtered at local abattoir. The compact oocyte complexes (COC’s) with evenly granulated ooplasm were vitrified using 4 different concentrations viz. 10, 15, 20, 25% of EG and DMSO with 1 and 3 min of ET. After 7 days of cryopreservation, the vitrified oocytes were thawed and these oocytes were evaluated for morphologically normal recovery, partial cumulus loss and different damages. The normal recovery was observed higher in 25% of EG and DMSO (3 min ET), partial cumulus loss found higher in 25% EG and DMSO (3 min ET) and damaged oocyte was observed higher in 15% EG and DMSO (1 min ET). Among all damages, the cracked zona was prevalent and observed significantly higher in 10% EG and DMSO (1 min ET)- 93.7% , shrinkage change in shape were found higher in 15% EG and DMSO (1 min ET)22.2%, and split in 2 halves were observed in 15% EG and DMSO (1 min ET)- 15.6%. The damage percent was significantly higher in 10% EG and DMSO (1 and 3 min ET) than other concentrations (P< 0.05). However, better results were obtained in 25% concentration compared to other concentrations of EG and DMSO.